Proteomic Profiling Methods and Protocols - Posch, Anton; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume presents the latest developments of the main pillars of protein analysis, such as sample preparation, separation, and characterization. The book begins by describing basic but important sample preparation protocols. It then goes on to describe more sophisticated procedures on enriching specific protein classes, and concludes with detailed descriptions of integrated work-flows for comprehensive protein analysis and characterization. The authors of the individual chapters are renowned protein biochemists who have all set value to provide a detailed representation of their lab work. Throughout the chapters, these authors share important tips and tricks for a successful and reproducible employment of their protocols in other laboratories. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Proteomic Profiling: Methods and Protocols is the perfect guide for students of Biochemistry, Biomedicine, Biology, and Genomics and will be an invaluable source for the experienced, practicing scientists.
Mechanical/Physical Methods of Cell Disruption and Tissue Homogenization -- Sample Preservation Through Heat Stabilization of Proteins: Principles and Examples -- Isolating Peripheral Lymphocytes by Density Gradient Centrifugation and Magnetic Cell Sorting -- Investigating the Adipose Tissue Secretome: A Protocol to Generate High Quality Samples Appropriate for Comprehensive Proteomic Profiling -- Methods for Proteomics-Based Analysis of the Human Muscle Secretome Using an in vitro Exercise Model -- Urinary Pellet Sample Preparation for Shotgun Proteomic Analysis of Microbial Infection and Host Pathogen Interactions -- A Protocol for the Parallel Isolation of Intact Mitochondria from Rat Liver, Kidney, Heart and Brain -- Isolation of Mitochondria from Cultured Cells and Liver Tissue Biopsies for Molecular and Biochemical Analyses -- Dynamic Range Compression with ProteoMiner: Principles and Examples -- Qualitative and Quantitative Proteomic Analysis of Formalin-Fixed Paraffin-Embedded (FFPE) Tissue -- Full-Length Protein Extraction Protocols and Gel-Based Downstream Applications in Formalin-Fixed Tissue Proteomics -- Enrichment of Low-Abundant Protein Targets by Immunoprecipitation Upstream of Mass Spectrometry -- P Isolation of Extracellular Vesicles for Proteomic Profiling -- A Protocol for Exosome Isolation and Characterization: Evaluation of Ultracentrifugation, Density-Gradient Separation, and Immunoaffinity Capture Methods -- Chloroplast Isolation and Affinity Chromatography for Enrichment of Low Abundant Proteins in Complex Proteomes -- Depletion of RuBisCO Protein Using the Protamine Sulfate Precipitation Method -- Step by Step Preparation of Proteins for Mass Spectrometric Analysis -- Identification of Protein N-Termini Using TMPP or Dimethyl Labeling and Mass Spectrometry -- Optimization of Cell Lysis and Protein Digestion Protocols for Protein Analysis by LC-MS/MS -- Comprehensive Protocol to Simultaneously Study Protein Phosphorylation, Acetylation and N-Linked Sialylated Glycosylation -- Protein Profiling and Phosphoprotein Analysis by Isoelectric Focusing -- Principles and Examples of Gel-Based Approaches for Phosphoprotein Analysis -- Neutral Phosphate-Affinity SDS-PAGE System for Profiling of Protein Phosphorylation -- Enrichment and Identification of Bacterial Glycopeptides by Mass Spectrometry -- In-Gel Peptide IEF Sample Preparation for LC/MS Analysis -- Western Blotting Using In-Gel Protein Labeling as a Normalization Control: Stain-Free Technology -- 2-D Western Blotting for Evaluation of Antibodies Developed for Detection of Host Cell Protein -- Free Flow Electrophoresis for Separation of Native Membrane Protein Complexes -- Three-Dimensional Electrophoresis for Quantitative Profiling of Complex Proteomes -- A Bead-Based Multiplex Sandwich Immunoassay to Assess the Abundance and Posttranslational Modification State of β-Catenin -- Identification of SUMO E3 Ligase Specific Substrates Using the HuProt Human Proteome Microarray -- Amyloid-Binding Proteins: Affinity Based Separation, Proteomic Identification and Optical Biosensor Validation -- Proteomic Profiling by Nanomaterials-Based Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry for High-Resolution Data and Novel Protein Information Directly from Biological Samples.
Keywords: Proteins .; Proteomics; Protein Science; Proteomics